Spectroscopic Assessment of boric acid levels in samples of instant noodles - Almeda, Ma. Cecilia V. (Asia-Pacific Journal of Science, Mathematics, and Engineering, 2015)
Boron, in the form of borates and boric acid, is a substance with a much checkered history in terms of its being a beneficial element to humankind due to its aility to preserve foods without any apparent harmful effect to human health. However, after some time, reports from the results of studies that started in the 1980s revealed that boron is beneficial to plants and animals but might be a factor in some human disorders such as disturbed macromineral metabolism. When present in excess amounts in the body, it may pose adverse effects to health such as illness in the stomach, kidney, liver and etc. Previous studies showed that most instant foods like fish balls and noodles contain different levels of boric acid among factories and production periods due to the lack of the stnadard measurement during the processing. Te mean boric acid content of represtative samples of four brands of instant noodles commonly available in local grocery stored was assessed by spectroscopic method. The values exceeded the allowed daily intake value set by the European Safety Authority.